FORMATION OF FAMILY EDUCATORS AS AN EFFORT TO REDUCE HOUSEHOLD FOOD WASTE AMONG POSYANDU CADRE GROUPS IN NAMBO DISTRICT KENDARI CITY - Nurmaladewi, Nurmaladewi; Jufri, Nurnashriana; Nirmala, Fifi; Rusliafa, Jusniar; Kohali, Rizki Eka Sakti Octaviani (LPPM Univ. Ibn Khaldun Bogor, 2024)
Food waste represents one of the most pressing global challenges, with significant implications for the environment, the economy, and social well-being. One of the key measures that communities can adopt to address household food waste is by transforming perceptions and practices surrounding food waste—viewing it not as waste to be discarded but as an alternative resource. The primary objective of this initiative is to enhance the role of Posyandu (integrated health post) cadres as family educators in providing community education. These educators are expected to explain the negative impacts of food waste on the environment and food security while offering practical guidance on sustainable practices, such as mindful shopping, proper food storage, and repurposing food leftovers into valuable products like eco-enzyme solutions. The training commenced with a pre-test to assess participants' baseline knowledge, involving 55 participants, including Posyandu cadres, representatives from public health centers (Puskesmas), sub-district officials, and the program team. The content delivered by the facilitators ranged from the selection of hygienic food ingredients to the practical steps for producing eco-enzymes from food waste. Practical modules were distributed to help participants easily implement the knowledge acquired during the sessions. Post-test results indicated a significant improvement in participants' understanding, coupled with high levels of enthusiasm during the discussion sessions. As a follow-up, program evaluations and additional training sessions will be conducted to ensure the sustainability of these efforts. This initiative is expected to support public health and environmental preservation through the prudent management of food and food waste.